FORMATION OF DEONTOLOGICAL COMPETENCE AMONG FUTURE TEACHERS - Shodieva Ranokhon Abdumadzhid kizi; Morkhova Inessa Vyacheslavovna (Galaxy International Interdisciplinary Research Journal, 2024)
An important condition for increasing the effectiveness of the interaction of teachers with maladapted students is the strengthening of the deontological orientation of pedagogical activity, which determines the relevance of the problem of developing the deontological readiness of future teachers to interact with maladapted adolescents of various categories (students with special needs of psychophysical development, gifted adolescents, students in dysfunctional, socially unprotected and dysfunctional families left without parental care, orphans, teenagers with deviant behavior, foreign students, etc.).